Comparative evaluation between E-Glass and hemp fiber composites application in rotorcraft interiors. (February 2015) - Scarponi, Claudio; Messano, Marco
Abstract: The present paper describes concepts and a preliminary project of a helicopter device, to investigate the use of natural fiber composites for semi-structural applications, such as electronic racks. The aim of the study consists on the evaluation of the substitution of the steel electronic rack, mounted on the helicopter Eurocopter AS 350 Écureuil, with a new version, utilizing hemp fabric/epoxy composite material. This replacement will permit to have an environmental friendly product and lower disposal costs and weight. Lower weight for helicopters and more in general for aircraft means lower fuel consumption, lower pollution and costs. The new rack has been designed using structural static and dynamic analysis through Finite Element Method (FEM). Results are promising from the structural point of view. In fact, a weight reduction of 8.01 kg (55.6%) with respect to steel has been obtained without significantly increasing the production cost. A comparison with glass fabric/epoxy composites is also provided. The results for both the composite materials are very similar, but the advantages for the environment demonstrate that is worthy choosing natural fiber composites configuration.